Fungsi dan Strategi Tuturan dalam Buku Bahasa Indonesia Sekolah Dasar: Penguatan Kompetensi Komunikatif - Finus Setia Sudarmi; Benedictus Sudiyana; Suwarto Suwarto (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to describe the function of speech actions and their delivery strategies in class VI Indonesian textbooks, with an emphasis on directive speech actions. The focus of this research is based on the importance of the role of speech actions in language learning, especially in helping students understand the context of polite, effective, and communicative language use. The research approach used is descriptive qualitative with a content analysis method. Data was obtained from the book Children Changing the World published by the Ministry of Education and Culture in 2022 as the main source, and is complemented by supporting data from grade VI students of SD Negeri 06 Ngringo. Analysis is carried out through the stages of identification, classification, and interpretation of the forms, functions, and strategies of speech actions found in the text. The results of the study show that in the book there are various types of directive speech actions such as commands, requests, invitations, advice, and prohibitions. The delivery strategies used include direct, indirect, and emotionally strengthened strategies. Direct strategies are more commonly used in the context of instructional learning, while indirect and emotional strategies are used to foster politeness and closeness of meaning between the writer and the reader. These findings show that speech acts in Indonesian textbooks not only function as a means of conveying information, but also as a medium for the formation of polite and communicative language characters for elementary school students.